Про деякі особливості сімейної комунікації: український контекст (1997–2023 рр.) - Kuznecova, Tetjana (Wiener Slawistischer Almanach, 2024)
The article presents the results of a sociolinguistic study into linguistic features of family communication among 100 bilingual families living in the Sumy region, the north eastern region of Ukraine. The focus is on the use of set expressions before (1997) and after (2023) the beginning of the full-scale invasion of Ukraine by troops of the Russian Federation on 24th February 2022. Trends in the elimination of precedent-setting texts in Russian from Soviet discourse, such as phrases from Soviet films and Soviet popular songs, as well as from works of Russian literature, and the appearance of new set expressions in Ukrainian from Ukrainian folklore, Ukrainian literature, and Ukrainian pop culture in family communication were studied. Precedent texts from childhood (quotes from children’s cartoons, films, television shows, literature) and individual authorial expressions turned out to be the most resistant to changes in family communication. The recent events in Ukraine have also led to the enrichment of the family lexicon with wartime phraseological units – both Ukrainian and Surzhik (mixed language). As a rule, they are used to express the emotions and feelings of Ukrainians, their attitude towards the enemy, and contain narratives about the resilience of the Ukrainian people.